Method for producing hydrogen using oxidized nanodiamond as photocatalyst
By using oxidized nanodiamond as a photocatalyst, the aqueous solution is contacted with it under light irradiation, which solves the problem that it is difficult to effectively produce hydrogen by sunlight in the prior art, and achieves an efficient water-photodissociation reaction.
Patent Information
- Application Number
- CN202380053561.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-13
- Filing Date
- 2023-07-12
- Publication Date
- 2025-02-28
AI Technical Summary
Existing photocatalytic technologies are difficult to efficiently produce hydrogen from water through sunlight and often require the use of precious metal cocatalysts or complex treatment steps.
Oxidized nanodiamond is used as a photocatalyst, and the aqueous solution is brought into contact with the oxidized nanodiamond under light irradiation, thereby achieving photodissociation of water to produce hydrogen.
Without the need for a cocatalyst, by using an oxidized nanodiamond photocatalyst, hydrogen can be produced from water under sunlight, thereby improving the efficiency of the photocatalytic reaction.
Smart Images

Figure HDA0005239823570000011 
Figure HDA0005239823570000012 
Figure HDA0005239823570000021
Abstract
Description
Technical Field
[0001] The present invention relates to the general technical field of nanomaterials, and more particularly to nanomaterials for photocatalysis, in particular for the production of hydrogen (H2) by the light-induced dissociation of water, a process known as "water splitting".
[0002] In fact, the present invention proposes the use of nanoparticles of oxidized diamond or nanodiamond as a photocatalyst. In other words, the present invention proposes a method for producing hydrogen from water, which comprises the step of contacting an aqueous solution with nanoparticles of oxidized diamond under light irradiation. The present invention also relates to a specific photocatalytic composition comprising oxidized nanodiamond and at least one other (photo)catalyst. Background Art
[0003] Due to the increasing demand for energy on the one hand and the reduction of fossil fuels such as coal, oil and natural gas on the other hand, there has been particular interest in hydrogen (H2), which has several advantages over fossil fuels.
[0004] First, the combustion of H2 produces only water (H2O), in contrast to fossil fuels, the combustion of which emits carbon dioxide (CO2), thus participating in global warming.
[0005] Furthermore, in order to avoid the production of H2 from natural gas (which also results in the production of CO2), alternatively, renewable solutions that are less harmful to the environment have been proposed, including the production of H2 by photocatalysis of water. In this method, H2 is produced by the dissociation of water induced by photons, i.e. under light irradiation, which can be used directly for combustion in fuel cells, for chemical or petrochemical processes, or in particular for storage in liquid form.
[0006] Processes for the photocatalytic production of H 2 are known from the prior art.
[0007] Photocatalysis is based on the principle of activating a semiconductor or a group of semiconductors such as a photocatalyst using energy provided by irradiation.
[0008] Semiconductors are characterized by their band gap between the valence band and the conduction band, which is unique to semiconductors. Any photon with energy greater than its band gap can be absorbed by the semiconductor. Conversely, any photon with energy less than its band gap cannot be absorbed by the semiconductor.
[0009] Photocatalysis can be defined as the absorption of photons with energy greater than the band gap width, which in the case of semiconductors induces the formation of electron-hole pairs. Thus, electrons are excited at the conduction band and holes are formed at the valence band. Such electron-hole pairs are able to form free radicals that either react with compounds present in the medium (such as H2O) to initiate redox reactions, or recombine according to various mechanisms.
[0010] It is therefore desirable to have a high-performance photocatalyst for producing H2 by the dissociation of water (particularly by using sunlight), which photocatalyst must:
[0011] a) having an energy band structure suitable for generating charge carriers that will enable oxidation and reduction reactions to occur on the surface of the photocatalyst to produce H2 from protons obtained from the oxidation of water by photogenerated holes;
[0012] b) have the best possible absorption of sunlight and low recombination of photogenerated charge carriers to ensure the best efficiency of the photocatalytic reaction;
[0013] c) It is available in large quantities, low in cost, and environmentally friendly, which greatly limits the use of metal particles (such as platinum particles), rare earth oxides, etc.; and
[0014] d) remain valid during operation.
[0015] In view of these limitations, it is therefore of interest to develop photocatalysts that are, on the one hand, nanosized to obtain a larger total surface area and, on the other hand, are semiconductors with positions of conduction and valence bands for photogenerated charges, whose energy levels are suitable for the oxidation of water and the reduction of protons, and whose band gap energies are suitable for the wavelength of visible light.
[0016] In the literature, a number of materials have been identified as photocatalysts for the production of H2 by the dissociation of water. Titanium dioxide (TiO2) with anatase structure is certainly the most studied semiconductor due to certain properties that favor this reaction, in particular (i) its photostability in water, (ii) the suitable position of its valence band that easily enables the first step of the oxidation of water (H2O→2H + +1 / 2O2+2e - ), (iii) acceptable charge carrier behavior, (iv) its non-toxicity and (v) its relatively modest cost compared to other types of photocatalysts.
[0017] However, the main limitation of TiO2 is its large band gap (3.1eV to 3.2eV), which requires activation with wavelengths below 400nm (UV range), which greatly limits the use of natural sunlight, which consists of about 40% visible light, which is not energetic enough and is therefore ineffective for activating TiO2. In addition, due to the difficulty in performing the half-reaction of reduction to hydrogen (2H + +2e - →H2), usually rare and expensive precious metals are added as promoters to facilitate catalytic reduction to produce hydrogen.
[0018] Many strategies have been implemented to overcome these limitations, such as modifying the composition, morphology, chemical structure, size, surface area, deposition, formation of surface plasmon properties, and coupling with other semiconductors (forming heterojunctions) to induce favorable electronic, optical, or chemical effects.
[0019] Nanomaterials containing diamond have also been proposed as photocatalysts. They are usually used in the form of hybrids or composites.
[0020] Therefore, in 2016, Lin et al. proposed integrating p-type copper(I) oxide nanocrystals into nanodiamonds for broad-spectrum photocatalytic hydrogen evolution [1].
[0021] International application WO 2016 / 193464 A1 describes the use of a photocatalytic composite comprising at least one semiconductor compound having a band gap in the range from 2 eV to 5 eV and diamond nanoparticles, the surface of which is advantageously hydrogenated [2].
[0022] In other prior art composites, not for water photocatalysis but for water decontamination, nanodiamonds, optionally doped with boron, are implemented together with graphitic carbon nitride (or g-C3N4) [3], optionally in association with silver nitrate (AgNO3) [4].
[0023] A single study in the literature reports the production of hydrogen by dissociating water with nanodiamond alone [5]. However, in this work, a pulsed laser with a wavelength of 532 nm and high power (80 mJ / pulse) was used. There is no indication that such materials can be used to dissociate water by using the spectrum of sunlight, which has a much lower power. Furthermore, it is clear from [5] that the use of nanodiamonds with hydrogenated surfaces is preferred, since hydrogenation significantly increases the quantum efficiency, suggesting that the sites with hydrogen termination act as electron reservoirs.
[0024] The goal set by the inventors was to propose a photocatalyst that allows the production of H2 from water by using sunlight as a source of photons, without the need to use co-catalysts (such as precious metals) or complex treatments such as hydrogenation. Summary of the invention
[0025] The invention allows to achieve the objectives set by the inventors. In fact, the inventors have shown that by using oxidized diamond nanoparticles as photocatalysts, it is possible to dissociate water under light irradiation to produce hydrogen.
[0026] On the one hand, the oxidized nanodiamonds can be used without adding other photocatalysts or co-catalysts (such as metal particles). In other words, in the method according to the present invention, the oxidized nanodiamonds can be used as the only photocatalyst.
[0027] As a reminder, diamond is a broadband semiconductor (5.5 eV) and is therefore theoretically unsuitable for absorbing visible light. However, in the form of nanoparticles, the light absorption properties of diamond are altered by optical effects associated with the nanosize or by the introduction of structural defects during its synthesis.
[0028] Furthermore, the inventors' work has shown that this effect exists for nanodiamonds with oxidized surfaces. Depending on its surface chemistry, the energy band diagram of the nanodiamond changes. A diamond surface saturated with hydrogen has a more negative conduction band and valence band edge electrochemical potential than a diamond surface saturated with oxidized functionalities. This is Figure 1 is shown for bulk diamond.
[0029] Therefore, the most reducing structure (i.e. hydrogenated diamond) is not the most favorable for producing H2. This is counter-intuitive to those skilled in the art. Instead, the inventors have shown that oxidized nanodiamonds must be used to maximize hydrogen production.
[0030] More particularly, the present invention relates to the use of oxidized nanodiamonds as photocatalysts for the production of hydrogen. Such hydrogen production is obtained under solar, natural or artificial illumination (or light).
[0031] In other words, the present invention relates to a method for producing hydrogen by photodissociation of water, comprising at least one step of contacting an aqueous solution with oxidized nanodiamonds under light irradiation, ie under solar, natural or artificial lighting (or light).
[0032] The expressions "photodissociation of water", "(photo)dissociation of water under light irradiation", "photocatalysis of water" and "(photo)catalysis of water under light irradiation" are equivalent in this manuscript and are used interchangeably.
[0033] Likewise, the expressions "under solar, natural or artificial illumination," "under solar, natural or artificial light," and "under solar, natural or artificial irradiation" are equivalent and used interchangeably in this manuscript.
[0034] The present invention implements nanodiamonds, i.e. diamonds in nanoparticle form. These nanodiamonds can be obtained from natural diamonds or synthetic diamonds. Synthetic diamonds are usually obtained by high pressure and high temperature (HPHT) synthesis or by chemical vapor deposition (CVD).
[0035] More specifically, nanodiamonds can be obtained by (i) grinding natural or synthetic bulk diamond; (ii) by detonation, in particular as described in international application WO 2016 / 193464 A1 [2]; (iii) directly by HPHT growth or CVD.
[0036] The average size of the diamond nanoparticles implemented in the present invention is between 1 nm and 500 nm, ie between 1 nm and 200 nm, in particular between 2 nm and 100 nm, more particularly between 5 nm and 50 nm.
[0037] In specific embodiments, the diamond nanoparticles implemented in the present invention may be doped, in particular doped with nitrogen or phosphorus (n-type doping) or doped with boron (p-type doping).
[0038] As mentioned above, the nanodiamonds implemented in the present invention are oxidized, that is, oxidized on the surface. In other words, the surface of the oxidized nanodiamond has more oxygen atoms than the surface of the non-oxidized nanodiamond.
[0039] Typically, the oxidized nanodiamonds implemented in the present invention have an oxygen / carbon ratio of at least 5 atomic % as determined by XPS (photoelectron spectroscopy) without pre-treating the oxidized nanodiamonds, such as annealing, to dehydrate.
[0040] In order to obtain oxidized nanodiamonds, these nanodiamonds must be subjected to an oxidation treatment.
[0041] The oxidation treatment aims to oxidize the surface of the nanodiamond by fixing and / or introducing the same or different oxygen-rich groups (i.e. the same or different groups containing at least one oxygen atom) on the surface of the nanodiamond. In the present invention, the group containing at least one oxygen atom is particularly selected from the group consisting of carboxyl (-C(=O)OH), hydroxyl (-OH), carbonyl (-C(=O)-) and peracid group (-C(=O)-O-OH).
[0042] This oxidation treatment is based on two broad types of surface modifications based on:
[0043] - physical treatments, such as plasma treatments (radio frequency, microwaves), UV treatments, X- or gamma-ray treatments, treatments with irradiation with electrons and heavy ions, wherein these various physical treatments can be carried out under CO 2 or under an oxygen-containing atmosphere, such as, for example, under air, under O 2 , under O 2 / argon or under ozone, such as, for example, UV treatments under ozone;
[0044] - Chemical treatments, such as treatment with alcoholic potash, hot or cold treatment with a mixture of sulfuric acid (H2SO4) and nitric acid (HNO3), treatment with a mixture of sulfuric acid (H2SO4) and hydrogen peroxide (H2O2) (also known as "piranha mixture"), treatment with a mixture of H2O2 and iron (also known as "Fenton's reagent"), treatment with strong acids (HCl, H2SO4, HNO3, HClO4), treatment with soda, treatment with strong oxidants (KMnO4, K2Cr2O7, KClO3 or CrO3 in hydrochloric acid, sulfuric acid or nitric acid), treatment with molten salts (KNO3), treatment with ozone and thermal treatment under CO2 or in an oxygen-containing atmosphere (such as, for example, under air, under O2, under O2 / argon or under ozone).
[0045] The oxidation treatment described above can be carried out at atmospheric pressure and / or ambient temperature (Tamb) or at a pressure greater than atmospheric pressure and / or at a temperature greater than ambient temperature (particularly in the case of heat treatment). "Ambient temperature" means a temperature of about 23°C (ie 23°C±5°C).
[0046] Advantageously, the oxidation treatment performed is a heat treatment under an oxygen-containing atmosphere (such as, for example, under air, under O2, under O2 / argon or under ozone). Advantageously, the heat treatment under an oxygen-containing atmosphere involves annealing at a temperature of 500°C ± 50°C for a duration of 1 hour to 5 hours, particularly 1 hour to 3 hours, under an oxygen-containing atmosphere (such as, for example, under air, under O2, under O2 / argon or under ozone, particularly under air). The following experimental section illustrates this heat treatment. Therefore, the method according to the present invention can provide a preliminary step for preparing oxidized nanodiamonds, which involves subjecting the nanodiamonds to an oxidation treatment as defined above. Typically, once the oxidation treatment has been performed, the oxidized nanodiamonds are placed in suspension again. This involves subjecting the oxidized nanodiamonds to an ultrasonic treatment and then centrifuging, thereby obtaining a colloidal suspension of oxidized nanodiamonds.
[0047] Prior to the ultrasonic treatment, the oxidized nanodiamonds are contacted with an aqueous solution. Such a solution has a water-based solvent as a solvent, thus justifying the name of an aqueous solution. In the context of the present invention, "water" refers to tap water, deionized water, distilled water or ultrapure water (18.2 MΩ.cm at 25°C).
[0048] Typically, the amount of oxidized nanodiamond used during contact with the aqueous solution prior to ultrasonic treatment is between 1 g / L aqueous solution and 50 g / L aqueous solution, i.e. between 10 g / L aqueous solution and 40 g / L aqueous solution, in particular about 30 g / L aqueous solution (i.e. 30 g / L±5 g / L).
[0049] The ultrasonic treatment step is carried out at a temperature between 4°C and 20°C, i.e. between 6°C and 15°C, in particular at about 10°C (i.e. 10°C ± 2°C). Advantageously, a constant temperature bath is used during the ultrasonic treatment step. Furthermore, the ultrasonic treatment step lasts for 15 minutes to 3 hours, i.e. 30 minutes to 2 hours, in particular for about 1 hour (i.e. 1 hour ± 15 minutes).
[0050] A centrifugation step is performed to separate a colloidal suspension of oxidized nanodiamonds corresponding to the supernatant obtained after the centrifugation step of the oxidized nanodiamond clusters, which form the pellet obtained after the centrifugation step. To this end, the centrifugation step is performed at a value between 1500 g and 4000 g, i.e. between 2000 g and 3000 g, in particular at about 2400 g (i.e. 2400 g ± 200 g).
[0051] The centrifugation step is performed at a temperature between 4° C. and 20° C., i.e. between 6° C. and 15° C., in particular at about 10° C. (i.e. 10° C.±2° C.). Furthermore, the centrifugation step lasts for 15 minutes to 2 hours, i.e. 30 minutes to 1 hour, in particular about 40 minutes (i.e. 40 minutes±15 minutes).
[0052] The oxidized nanodiamonds are brought into contact during step a) with an aqueous solution as defined above.
[0053] In a specific embodiment, the solvent of the aqueous solution carried out during step a) comprises only water, ie the solvent consists of water, in particular of ultrapure water (18.2 MΩ.cm at 25° C.).
[0054] Typically, the amount of oxidized nanodiamonds used during placement in contact with the aqueous solution is between 1 mg / L aqueous solution and 1 g / L aqueous solution, i.e., between 5 mg / L aqueous solution and 500 mg / L aqueous solution, particularly between 10 mg / L aqueous solution and 50 mg / L aqueous solution, and more particularly about 12.5 mg / L aqueous solution (i.e., 12.5 mg / L±1 mg / L).
[0055] The contact between the aqueous solution and the oxidized nanodiamonds can be carried out under stirring and / or in a continuous or discontinuous flow of an inert gas such as argon, nitrogen, helium or a mixture thereof. Advantageously, the contact is carried out under stirring and a continuous nitrogen flow.
[0056] Typically, the contact between the aqueous solution and the oxidized nanodiamonds is carried out at a temperature between 5°C and 80°C, particularly between 15°C and 50°C, more particularly at ambient temperature.
[0057] During contacting, the oxidized nanodiamonds may be in the form of a suspension. Alternatively, during contacting, the oxidized nanodiamonds may be supported.
[0058] Any type of support conventionally used to retain photocatalysts in methods for water dissociation under light irradiation can be used in the context of the present invention. Illustrative examples include 2D supports (such as, for example, fabric sheets, especially fabric sheets made of optical fibers), surface coatings (such as, for example, paint), and dense or porous 3D supports (such as, for example, foams or honeycombs).
[0059] The contact between the oxidized nanodiamond and the aqueous solution is carried out under light irradiation. This light irradiation can be natural (sunlight) or artificial, in particular by an irradiation device, such as a lamp, UV lamp, visible light lamp, UV-visible light lamp, IR lamp, excimer lamp, LED, laser, laser diode or supercontinuum fiber light source. Obviously, in the case of artificial solar irradiation, the irradiation device used reproduces the spectrum of sunlight and the power of sunlight.
[0060] Advantageously, the irradiance of the irradiation device is 25 mW / cm 2 Up to 150mW / cm 2 between 53.5 mW / cm 2 ±5mW / cm 2 In other words, "under light exposure" means under natural or artificial solar illumination (or light).
[0061] The radiation applied during the light irradiation may be one of UV radiation (wavelength 200 nm to 400 nm), visible light radiation (wavelength 400 nm to 800 nm), or near infrared radiation (wavelength 800 nm to 1200 nm), and combinations thereof.
[0062] Advantageously, the light irradiation performed in the method of the invention is natural light irradiation, ie natural solar lighting (or light).
[0063] In the context of the present invention, the aqueous solution may further comprise a sacrificial agent. Typically, the sacrificial agent implemented in the present invention is an electron donor agent that can be oxidized by molecular oxygen formed during the photodissociation reaction of water and can effectively increase the production yield of H2.
[0064] The sacrificial agent implemented in the method according to the invention is generally selected from the group consisting of amines and alcohols, more particularly selected from the group consisting of one of methanol, ethanol, triethanolamine (TEOA) and mixtures thereof. Advantageously, the sacrificial agent used in the context of the method according to the invention is TEOA or methanol.
[0065] When present, the sacrificial agent is present in an amount of 0.05% to 50% by volume relative to the volume of the aqueous solution, particularly in an amount of 0.1% to 1% by volume relative to the volume of the aqueous solution.
[0066] In certain embodiments, oxidized nanodiamonds are the only photocatalyst implemented in the method.
[0067] Alternatively, in another specific embodiment, the oxidized nanodiamond is used together with at least one other element selected from the group consisting of photocatalysts, catalysts, adsorbents and combinations thereof. Thus, the oxidized nanodiamond can be associated in a heterojunction with at least one other photocatalyst of inorganic, molecular (quantum dots and clusters) or organic (colorants) photocatalyst type, and / or with at least one catalyst of metallic, inorganic or molecular (quantum dots and clusters) catalyst type, and / or with at least one adsorbent, such as activated carbon or metal organic framework (MOF), which improves material adsorption and charge transfer, wherein these adsorbent materials may also have semiconductor properties, such as certain MOFs. In this alternative, the oxidized nanodiamond and other elements selected from the group consisting of photocatalysts, catalysts, adsorbents and combinations thereof form a catalytic composition. Advantageously, the catalytic composition does not include any platinum or other precious metals.
[0068] Any semiconductor or molecular type of photocatalyst known to those skilled in the art and used in the process of photodissociation of water to produce H2 can be used in the context of the present invention.
[0069] However, in a particular embodiment of the method according to the invention, the photocatalyst associated with the oxidized nanodiamonds does not comprise graphitic carbon nitride.
[0070] Advantageously, the photocatalyst implemented with the oxidized nanodiamond is selected from the group consisting of transition metals, derivatives of transition metals, metal carbides, metal nitrides, metal oxides, metal sulfides. In particular, the photocatalyst implemented with the oxidized nanodiamond is selected from the group consisting of transition metal oxides and transition metal sulfides. In particular, the plurality of photocatalysts implemented with the oxidized nanodiamond is selected from the group consisting of TiO2, TiO2-B (in the form of titanate sheets), ZnO, WO3 and Fe2O3.
[0071] When used with oxidized nanodiamonds, the photocatalyst, catalyst and / or adsorbent may be in dispersed form, in particular in the form of nanoparticles. The average size of these nanoparticles is between 1 nm and 1000 nm, i.e. between 2 nm and 200 nm, in particular between 3 nm and 100 nm, more particularly between 4 nm and 50 nm, in particular between 5 nm and 20 nm.
[0072] Alternatively, the photocatalyst, catalyst and / or adsorbent may be used in aggregated form.
[0073] The present invention also relates to a photocatalytic composition for use in the method according to the present invention. The photocatalytic composition comprises oxidized nanodiamonds and at least one other element selected from the group consisting of photocatalysts, catalysts, adsorbents and combinations thereof, and the photocatalytic composition does not include any graphitic carbon nitride.
[0074] In the photocatalytic composition according to the present invention, the oxidized nanodiamond is present in an amount between 0.1 wt % and 80 wt %, i.e. between 1 wt % and 50 wt %, in particular between 2 wt % and 30 wt %, relative to the amount of at least one other element selected from the group consisting of photocatalysts, catalysts, adsorbents and combinations thereof.
[0075] Other characteristics and advantages of the invention will also emerge on reading the following examples given for illustrative and non-limiting purposes and with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 presents the energy band diagrams of hydrogenated and oxidized diamond compared with other semiconductors [6].
[0077] Figure 2 The size distribution of dynamic light scattering (DLS) of oxidized nanodiamonds prepared as described in point I below is presented.
[0078] Figure 3 The Fourier transform infrared absorption spectrum of oxidized nanodiamond prepared as described in point I below is presented.
[0079] Figure 4 XPS analysis of oxidized nanodiamonds prepared as described in point I below is presented.
[0080] Figure 5 A comparison of the average rates of H2 production by photocatalytic dissociation of water under artificial solar irradiation in the presence of 10 mg of "plasma-chemically" oxidized nanodiamonds (2 replicate tests) or P25TiO2 (Evonik) and 1 vol% TEOA (sacrificial agent) is presented.
[0081] Figure 6 The average rate of H2 production by photocatalytic dissociation of water under artificial solar irradiation in the presence of 10 mg of "plasma-chemically" oxidized nanodiamonds is presented as a function of the concentration of TEOA (sacrificial agent).
[0082] Figure 7 The average rate of H2 production by photocatalytic dissociation of water under artificial solar irradiation in the presence of 1 vol% TEOA (sacrificial agent) is presented, depending on the concentration of nanodiamonds oxidized by "plasma chemistry". DETAILED DESCRIPTION
[0083] I. Preparation of Oxidized Nanodiamonds .
[0084] The diamond nanoparticles used were synthesized by detonation and obtained from PlasmaChem (Germany).
[0085] First, the diamond nanoparticles were oxidized by annealing in air and at atmospheric pressure according to the following protocol:
[0086] - Place 2 crucibles in the center of the tube furnace, each filled with 200 mg of untreated nanoparticles;
[0087] - Raise the temperature of the furnace from Tamb to 200°C at a temperature ramp of 20°C / min, and then keep the nanoparticles at 200°C for 15 minutes;
[0088] - Raise the temperature of the furnace from 200°C to 500°C with a temperature ramp of 30°C / min, and then keep the nanoparticles at 500°C for 1 hour and 30 minutes;
[0089] - The two crucibles are then removed “while hot” using tongs and placed under a Tamb, in order to cool the nanoparticles as quickly as possible and thus stop the annealing;
[0090] - When the nanoparticles were returned to Tamb, they were weighed. A loss of approximately 50% of the initial mass was generally observed.
[0091] The nanoparticles were then placed in suspension according to the following scheme:
[0092] - Place 100 mg of oxidized nanoparticles in a Falcon 15 mL centrifuge tube;
[0093] - Add 3 mL of ultrapure water (18.2 MΩ.cm);
[0094] - Bring the solution to a temperature of 10°C in a thermostatic bath;
[0095] - The solution was then sonicated using a cup horn device (Bioblock Scientific 750W, 60% amplitude, cycle 1 sec on / 1 sec off, duration 60 min) while maintaining the temperature at 10°C;
[0096] - After sonication, the solution was then centrifuged (2400 g, 40 min) to remove the largest clusters;
[0097] - Immediately after centrifugation, the supernatant containing the nanoparticles in colloidal suspension was removed by pipetting (about 2.5 mL of the initial 3 mL);
[0098] - The suspension is then stored in a plastic bottle at ambient temperature, protected from light. This storage can be carried out for a long period of time, i.e. more than 1 year.
[0099] The concentration of nanoparticles in the suspension was determined by drying 100 μL of the suspension under Tamb overnight and measuring the mass of the dry residue.
[0100] II. Characterization of oxidized nanodiamonds.
[0101] II.1. method.
[0102] - The hydrodynamic diameter of the suspended objects was measured by dynamic light scattering (DLS) on 1 mL of suspension (1 mg of nanoparticles / mL) (HORIBAS Z-100 Nanopartica series).
[0103] - The zeta potential of the suspended objects was measured by electrophoretic light scattering on 700 μL of suspension (1 mg of nanoparticles / mL) (HORIBA SZ-100 Nanopartica series).
[0104] - Characterization of the surface chemistry of the suspended nanodiamonds by Fourier transform infrared spectroscopy: 2 μL of the suspension (5 mg nanoparticles / mL) were evaporated on an ATR crystal of a Bruker Alpha II spectrometer.
[0105] - Chemical characterization of suspended nanodiamonds and determination of O / C ratio by XPS: 20 μL of the suspension (1 mg nanoparticles / mL) were evaporated on a silicon substrate coated with 50 nm gold. The analysis was performed on a Kratos Analytical Axis Ultra DLD (monochromatized Al Kα source).
[0106] II.2. result.
[0107] like Figure 2 As shown, the oxidized nanodiamond has a hydrodynamic diameter of 48 nm ± 10 nm and a zeta potential of 57 mV ± 5 mV in suspension.
[0108] Figure 3 The infrared absorption spectrum of the oxidized nanodiamond presented in the paper highlights the C=O bond (1750 cm -1 ) may involve carboxylic acid, and CO bonds (1000 cm -1 Up to 1300cm -1 ) is associated with alcohol or ester functional groups on the surface. It is also noted that at 3000 cm -1 Up to 3500cm -1 The shoulder between 2800 cm-1 and 2800 cm-2 reflects the presence of an OH bond associated with the carboxylic acid. In practice, the spectrum was recorded under a dry nitrogen flow and therefore there is no OH contribution from ambient humidity. Finally, it is important to note that the -1 Up to 3000cm -1 There is no absorption between them, which means there are no CH bonds on the surface of the particles.
[0109] XPS analysis highlights the presence of three elements in the oxidized nanodiamonds, namely carbon, oxygen and nitrogen ( Figure 4 ). The nitrogen is mostly located in the core of the nanoparticles and comes from the nitrogen explosive used during synthesis via detonation.
[0110] The atomic ratios of the various elements are given in Table 1 below.
[0111] carbon 87.5 atomic% oxygen 10.5 atomic% nitrogen 2 atomic%
[0112] Table 1
[0113] III. Photocatalytic behavior of oxidized nanodiamonds.
[0114] III.1. Operating procedures.
[0115] To study the photocatalytic behavior of oxidized diamond nanoparticles, our experiments involved the use of a photocatalytic system reproducing the solar spectrum and having a power of 150 W (corresponding to 53.5 W / cm for the nanodiamond suspension) in the presence of a small proportion of an antioxidant / sacrificial agent (triethanolamine or TEOA). 2 A suspension of nanodiamonds (NDs) placed under a continuous inert gas (N2) flow was continuously illuminated by a lamp (Spatite Hit150G12 8800K (Art-nr 226224)) with an irradiance of 100 Å. The experiments were performed under Tamb while the temperature of the suspension was controlled throughout the photocatalytic test.
[0116] The produced hydrogen was quantified by online measurement by gas chromatography for 2 h after the production of hydrogen had stabilized. Thus, the formation kinetics of the produced H2 could be followed.
[0117] The experimental conditions were as follows: the photocatalyst (10 mg or 20 mg) was suspended in 800 mL ultrapure H2O (mQ), TEOA (0.1, 1 vol% TEOA), magnetically stirred at 700 rpm, and a continuous flow of N2 at 100 cm 3 / minute, and the analysis duration after stabilization was 2 hours, with analysis collected every 2.5 minutes.
[0118] III.2. result.
[0119] Figure 5 It was shown that at the same concentration, oxidized nanodiamonds (PlasmaChem) performed as well as the reference commercial photocatalyst TiO2 P25 (Evonik).
[0120] It was also observed that the generation of H2 correlated with the concentration of the sacrificial agent ( Figure 6 ), but not in proportion, which indeed confirms that H2 is produced by the solar photolysis of water and that TEOA mainly acts as a trap for O2.
[0121] In addition, the optimal concentration of oxidized nanodiamonds seems to be around 10 mg or 12.5 mg / L ( Figure 7 ).
[0122] bibliography
[0123] [1]Lin et al,2016,“Nanodiamond-Embedded p-Type Copper(I)OxideNanocrystals for Broad-Spectrum Photocatalytic Hydrogen Evolution”,Adv.EnergyMater.,vol.6,1501865.
[0124] [2]International application WO 2016 / 193464on behalf of CNRS et al,published 8December 2016.
[0125] [3]Su et al,2019,“Heterostructured boron doped nanodiamonds@g-C3N4nanocomposites with enhanced photocatalytic capability under visiblelightirradiation”,Int J of Hydrogen Energy,vol.44,19805.
[0126] [4]Patent application CN 110639595 A on behalf of Henan InstEngineering,published 3 January 2020.
[0127] [5]Jang et al,2012,“Nanodiamonds as photocatalysts for reduction ofwaterand graphene oxide”,Chem.Comm.,vol.48,pages 696-698.
[0128] [6]Nebel,2013,“Photocatalysis:A source of energetic electrons”,Nat.Mater.,vol.12,pages 780-781.
Claims
1. Use of oxidized nanodiamonds as photocatalysts for hydrogen production under solar, natural or artificial illumination (or light).
2. A method for producing hydrogen by photodissociation of water, comprising at least one step of contacting an aqueous solution with oxidized nanodiamonds under solar, natural or artificial illumination (or light).
3. The method according to claim 2, characterized in that The oxidized nanodiamond has an oxygen / carbon ratio of at least 5 atomic % as determined by XPS (XPS) without pre-treating the oxidized nanodiamond.
4. The method according to claim 2 or 3, characterized in that: The method provides a preliminary step for preparing the oxidized nanodiamond, which preliminary step involves subjecting the nanodiamond to an oxidation treatment.
5. The method according to claim 4, characterized in that The oxidation treatment consists of annealing at a temperature of 500° C.±50° C. for a duration between 1 hour and 5 hours in an oxygen-containing atmosphere.
6. The method according to any one of claims 2 to 5, characterized in that The contacting between the aqueous solution and the oxidized nanodiamonds is carried out with stirring and / or under an inert gas, in particular with stirring and under a continuous nitrogen flow.
7. The method according to any one of claims 2 to 6, characterized in that The light irradiation is natural light irradiation.
8. The method according to any one of claims 2 to 7, characterized in that The aqueous solution comprises a sacrificial agent, in particular triethanolamine (TEOA) or methanol.
9. The method according to any one of claims 2 to 8, characterized in that The oxidized nanodiamonds were the only photocatalyst implemented.
10. The method according to any one of claims 2 to 8, characterized in that The oxidized nanodiamond is used together with at least one other element selected from the group consisting of a photocatalyst, a catalyst, an adsorbent, and combinations thereof.
Citation Information
Patent Citations
Production of dihydrogen with nanodiamond-supported photocatalyst
WO2016193464A1